On Complete Intuitionistic Fuzzy Roh-Ideals in Roh-Algebras - Atshan , Arkan Ajil; Khalil, Shuker Mahmood (Iraqi Journal of Science, 2023)
In this paper, we shall investigate and study some kinds of ideals in an intuitionistic fuzzy setting, they are called complete intuitionistic fuzzy subalgebra, complete intuitionistic fuzzy ideal, and complete intuitionistic fuzzy ideal. In this study, we have also proposed some hypotheses to explain some of the relationships between these kinds of intuitionistic fuzzy ideals.